2023
DOI: 10.1177/17427665231185697
|View full text |Cite
|
Sign up to set email alerts
|

China’s digital diplomacy on Twitter: The multiple reactions to the Belt and Road Initiative

Maximiliano Facundo Vila Seoane

Abstract: This article examines three aspects of China’s digital diplomacy efforts about the Belt and Road Initiative (BRI) on Twitter between February 9th 2019 to January 3rd 2020. First, it explores the frequency and geographical distribution of tweets about the BRI. Second, it scrutinises the main topics discussed in such tweets. Finally, it describes the actors producing BRI content. Results show that Chinese digital diplomacy has been proactive on Twitter, driven by the posting practices of its main international b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Specifically, Western media conveyed the initiative in a negative light, whilst Chinese media gave the opposite view (Teo & Xu, 2021;H. Yang & van Gorp, 2021;Vila Seoane, 2023;Zhang & Wu, 2017). In contrast, Kuteleva and Vasiliev (2021) found that Russian media reported on the BRI positively, reproducing the official state narrative of its contributions to Sino-Russian relations.…”
Section: Framing Chinamentioning
confidence: 99%
“…Specifically, Western media conveyed the initiative in a negative light, whilst Chinese media gave the opposite view (Teo & Xu, 2021;H. Yang & van Gorp, 2021;Vila Seoane, 2023;Zhang & Wu, 2017). In contrast, Kuteleva and Vasiliev (2021) found that Russian media reported on the BRI positively, reproducing the official state narrative of its contributions to Sino-Russian relations.…”
Section: Framing Chinamentioning
confidence: 99%